PENGARUH KOMPRES LIDAH BUAYA TERHADAP PENURUNAN INTENSITAS NYERI PADA IBU POSTPARTUM YANG MENGALAMI MASTITIS DI KLINIK PRATAMA KASIH IBU DELI TUA TAHUN 2022 - Gf Gustina Siregar; Eka Sriwahyuni; Yunita Syahputri Damanik (JURNAL ILMIAH DHDT - KEBIDANAN, 2023)
Problems that often arise in postpartum mothers' breasts are sore nipples, swollen nipples, mastitis or breast abscess. Mastitis cases are estimated to occur in the first 12 weeks, but can also occur until the second year of breastfeeding. Interventions that relieve symptoms of breast pain using nonpharmacological methods are aloe vera compresses. This research was conducted at the Pratama Kasih Ibu Clinic, Deli Tua, from February to June 2022. This type of research was a quasi-experimental using a one group pretest-posttest. The population determined in this study were postpartum mothers who experienced mastitis at the Pratama Kasih Ibu Clinic, Deli Tua. The number of available samples is 16 samples taken by purposive sampling from the population. The results of bivariate analysis of the effect of aloe vera compress on decreasing pain intensity of postpartum mothers who experience mastitis obtained p-value (0.000). From the results of the bivariate p-value <α (0.05) analysis, it can beconcluded that there is an effect of aloe vera compress on reducing painintensity in postpartum mothers who experience mastitis at the Pratama KasihIbu Clinic, Deli Tua in 2022. It is recommended to mothers postpartum to makemore use of non-pharmacological therapies such as aloe vera compresses toreduce the intensity of pain due to mastitis and reduce the use of medical drugsthat can cause side effects.